UJI AKTIVITAS ANTIHIPERGLIKEMIK EKSTRAK ETANOL DAUN TEMBELEKAN (Lantana camara L.) TERHADAP MENCIT PUTIH JANTAN TERINDUKSI ALOKSAN - Eka Setia Rini; Rudi Kartika; Rahmat Gunawan (JURNAL ATOMIK, 2016)
Phytochemical screening has been conducted on the ethanol extract of tembelekan leaves (Lantana camara Linn) which showed the presence of alkaloids, flavanoids, steroids, triterpenoids and phenolic. Testing antihyperglicemic activity of ethanol extract tembelekan leaves conducted experiments in the laboratory with each dose 14 mg/kg BW, 28 mg/kg BW and 56 mg/kg BW given orally in male mice induced by alloxan. Measurement of blood glucose levels done on day 0, 4, 8, 14 and 18 by using glucometer and glucose test strips. The decrease in blood glucose levels is 56,89 % with ethanol extract tembelekan leaves dose 56 mg/kg BW. The results showed that there is decrease in blood glucose because given ethanol extract tembelekan leaves.